Kajian Literatur: Pengaruh Pendekatan Konstruktivisme terhadap Kemampuan Pemahaman Konsep Matematis - Pratiwi, Vivied Eka Pratiwi; Lukman El Hakim (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
The aim of this research is to re-identify the influence of the constructivist approach on the ability to understand mathematical concepts. After that, the results of the analysis are combined and a conclusion is drawn about the problem as a whole. The method in this research is a literature review. This research is related to collecting, reading and storing library information, as well as processing library materials without involving field research. Data collection comes from journals indexed by Sinta and Google Scholar for the last 7 years. The keywords for the search are